Association of Fusobacterium nucleatum with immunity and molecular alterations in colorectal cancer - Nosho, Katsuhiko (World J Gastroenterol, 2016)
The human intestinal microbiome plays a major role in human health and diseases, including colorectal cancer. Colorectal carcinogenesis represents a heterogeneous process with a differing set of somatic molecular alterations, influenced by diet, environmental and microbial exposures, and host immunity. Fusobacterium species are part of the human oral and intestinal microbiota. Metagenomic analyses have shown an enrichment of Fusobacterium nucleatum (F. nucleatum) in colorectal carcinoma tissue. Using 511 colorectal carcinomas from Japanese patients, we assessed the presence of F. nucleatum. Our results showed that the frequency of F. nucleatum positivity in the Japanese colorectal cancer was 8.6% (44/511), which was lower than that in United States cohort studies (13%). Similar to the United States studies, F. nucleatum positivity in Japanese colorectal cancers was significantly associated with microsatellite instability (MSI)-high status. Regarding the immune response in colorectal cancer, high levels of infiltrating T-cell subsets (i.e., CD3+, CD8+, CD45RO+, and FOXP3+ cells) have been associated with better patient prognosis. There is also evidence to indicate that molecular features of colorectal cancer, especially MSI, influence T-cell-mediated adaptive immunity. Concerning the association between the gut microbiome and immunity, F. nucleatum has been shown to expand myeloid-derived immune cells, which inhibit T-cell proliferation and induce T-cell apoptosis in colorectal cancer. This finding indicates that F. nucleatum possesses immunosuppressive activities by inhibiting human T-cell responses. Certain microRNAs are induced during the macrophage inflammatory response and have the ability to regulate host-cell responses to pathogens. MicroRNA-21 increases the levels of IL-10 and prostaglandin E2, which suppress antitumor T-cell-mediated adaptive immunity through the inhibition of the antigen-presenting capacities of dendritic cells and T-cell proliferation in colorectal cancer cells. Thus, emerging evidence may provide insights for strategies to target microbiota, immune cells and tumor molecular alterations for colorectal cancer prevention and treatment. Further investigation is needed to clarify the association of Fusobacterium with T-cells and microRNA expressions in colorectal cancer.